Sensory Disturbances, but Not Motor Disturbances, Induced by Sensorimotor Conflicts Are Increased in the Presence of Acute Pain - Brun, Clémentine; Gagné, Martin; McCabe, Candida S.; Mercier, Catherine (Frontiers in Integrative Neuroscience, 2017)
Incongruence between our motor intention and the sensory feedback of the action (sensorimotor conflict) induces abnormalities in sensory perception in various chronic pain populations, and to a lesser extent in pain-free individuals. The aim of this study was to simultaneously investigate sensory and motor disturbances evoked by sensorimotor conflicts, as well as to assess how they are influenced by the presence of acute pain. It was hypothesized that both sensory and motor disturbances would be increased in presence of pain, which would suggest that pain makes body representations less robust. Thirty healthy participants realized cyclic asymmetric movements of flexion-extension with both upper limbs in a robotized system combined to a 2D virtual environment. The virtual environment provided a visual feedback about movements that was either congruent or incongruent, while the robotized system precisely measured motor performance (characterized by bilateral amplitude asymmetry and medio-lateral drift). Changes in sensory perception were assessed with a questionnaire after each trial. The effect of pain (induced with capsaicin) was compared to three control conditions (no somatosensory stimulation, tactile distraction and proprioceptive masking). Results showed that while both sensory and motor disturbances were induced by sensorimotor conflicts, only sensory disturbances were enhanced during pain condition comparatively to the three control conditions. This increase did not statistically differ across visual feedback conditions (congruent or incongruent). Interestingly however, the types of sensations evoked by the conflict in the presence of pain (changes in intensity of pain or discomfort, changes in temperature or impression of a missing limb) were different than those evoked by the conflict alone (loss of control, peculiarity and the perception of having an extra limb). Finally, results showed no relationship between the amount of motor and sensory disturbances evoked in a given individual. Contrary to what was hypothesised, acute pain does not appear to make people more sensitive to the conflict itself, but rather impacts on the type and amount of sensory disturbances that they experienced in response to that conflict. Moreover, the results suggest that some sensorimotor integration processes remain intact in presence of acute pain, allowing us to maintain adaptive motor behaviour.